High Spatiotemporal Resolution 4D Flow MRI of Intracranial Aneurysms at 7T in 10 Minutes - Gottwald, L.M.; Töger, J.; Markenroth Bloch, K.; Peper, E.S.; Coolen, B.F.; Strijkers, G.J.; van Ooij, P.; Nederveen, A.J. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Patients with intracranial aneurysms may benefit from 4D flow MR imaging because the derived wall shear stress is considered a useful marker for risk assessment and growth of aneurysms. However, long scan times limit the clinical implementation of 4D flow MR imaging. Therefore, this study aimed to investigate whether highly accelerated, high resolution, 4D flow MR imaging at 7T provides reliable quantitative blood flow values in intracranial arteries and aneurysms.MATERIALS AND METHODS: We used pseudospiral Cartesian undersampling with compressed sensing reconstruction to achieve high spatiotemporal resolution (0.5 mm isotropic, ∼30 ms) in a scan time of 10 minutes. We analyzed the repeatability of accelerated 4D flow scans and compared flow rates, stroke volume, and the pulsatility index with 2D flow and conventional 4D flow MR imaging in a flow phantom and 15 healthy subjects. Additionally, accelerated 4D flow MR imaging with high spatiotemporal resolution was acquired in 5 patients with aneurysms to derive wall shear stress.RESULTS: Flow-rate bias compared with 2D flow was lower for accelerated than for conventional 4D flow MR imaging (0.31 ± 0.13, P = .22, versus 0.79 ± 0.17 mL/s, P < .01). Pulsatility index bias gave similar results. Stroke volume bias showed no difference for accelerated as well as for conventional 4D flow compared to 2D flow MR imaging. Repeatability for accelerated 4D flow was similar to that of 2D flow MR imaging. Increased temporal resolution for wall shear stress measurements in 5 intracranial aneurysms did not show a consistent effect for the wall shear stress but did show an effect for the oscillatory shear index.CONCLUSIONS: Highly accelerated high spatiotemporal resolution 4D flow MR imaging at 7T in intracranial arteries and aneurysms provides repeatable and accurate quantitative flow values. Flow rate accuracy is significantly increased compared with conventional 4D flow scans.CScompressed sensingNcardnumber of reconstructed cardiac timeframesOSIoscillatory shear indexPROUDPROspective Undersampling in multiple DimensionsRacceleration factorSENSEsensitivity encodingUIAunruptured intracranial aneurysmWSSwall shear stressWSSPSpeak systolic WSSWSSTAtime-averaged WSS